A differential risk assessment and decision model for Transarterial chemoembolization in hepatocellular carcinoma based on hepatic function - Joon Yeul Nam (BMC Cancer, 2020)
Abstract Background The decision of transarterial chemoembolization (TACE) initiation and/or repetition remains challenging in patients with unresectable hepatocellular carcinoma (HCC). The aim was to develop a prognostic scoring system to guide TACE initiation/repetition. Methods A total of 597 consecutive patients who underwent TACE as their initial treatment for unresectable HCC were included. We derived a prediction model using independent risk factors for overall survival (OS), which was externally validated in an independent cohort (n = 739). Results Independent risk factors of OS included Albumin-bilirubin (ALBI) grade, maximal tumor size, alpha-fetoprotein, and tumor response to initial TACE, which were used to develop a scoring system (“ASAR”). C-index values for OS were 0.733 (95% confidence interval [CI] = 0.570–0.871) in the derivation, 0.700 (95% CI = 0.445–0.905) in the internal validation, and 0.680 (95% CI = 0.652–0.707) in the external validation, respectively. Patients with ASAR< 4 showed significantly longer OS than patients with ASAR≥4 in all three datasets (all P < 0.001). Among Child-Pugh class B patients, a modified model without TACE response, i.e., “ASA(R)”, discriminated OS with a c-index of 0.788 (95% CI, 0.703–0.876) in the derivation, and 0.745 (95% CI, 0.646–0.862) in the internal validation, and 0.670 (95% CI, 0.605–0.725) in the external validation, respectively. Child-Pugh B patients with ASA(R) < 4 showed significantly longer OS than patients with ASA(R) ≥ 4 in all three datasets (all P < 0.001). Conclusions ASAR provides refined prognostication for repetition of TACE in patients with unresectable HCC. For Child-Pugh class B patients, a modified model with baseline factors might guide TACE initiation.